GWARANCJE HARMONIJNEGO KSZTAŁTOWANIA SIĘ WZAJEMNYCH RELACJI PAŃSTWA POLSKIEGO I KOŚCIOŁA KATOLICKIEGO W KONKORDACIE Z 1993 ROKU - Góralski, Wojciech (Wydział Prawa i Administracji UAM, 2009)
The Concordat between the Holy See and the Republic of Poland concluded on 28 July 1993 and representing the new, post-Council model of such an agreement has been shaped in the spirit of the Second Vatican Council whose fundamental principle governing the relationship between the state and the church is the protection of religious freedom that is rooted in the right for personal dignity due to every person. The Concordat Agreement governs all matters of interest to both parties and the underlying principles of this relation are based on mutual understanding o f the respective purposes and tasks, thus providing for their autonomy. It strengthens the status quo established by the Act on the relationship of the state with the Catholic Church in the Republic of Poland of 17 May 1989, explicitly displays the will of the parties to sustain mutual concord and agreement, and their readiness to collaborate “for the promotion of the benefit of humanity and the good of the community” (article 1 of the Concordat). The fundamental principle governing the mutual relations of the Polish state and the Catholic Church adopted in the Concordat is the principle of securing either of them independence and autonomy, respective in their own domains (article 1). That principle has been subsequently incorporated in the Constitution of the Republic of Poland (article 25 section 3). The Concordat Agreement also includes provisions pursuant to which both parties assume certain obligations, and some others containing unilateral guarantees exchanged by both parties (these constitute the actual subject of this study). The bilaterality of the guarantees seems to provide conditions necessary for a harmonious formation of mutual relations of two communities: political and religious.
GUARANTEES OF HARMONIOUS SHAPING OF MUTUAL RELATIONS BETWEEN THE POLISH STATE AND THE CATHOLIC CHURCH IN THE CONCORDAT OF 1993